Sensitization to indoor allergens and frequency of asthma exacerbations in children - Irene Irene; Putu Siadi Purniti; Sumadiono Sumadiono (Paediatrica Indonesiana, 2011)
Background The rapid increase in asthma incidence has implicated the importance of environmental influences over genetic influences. Sensitization to perennial indoor allergens has been associated with increased asthma symptoms.Objective To examine the correlation between sensitization to indoor allergens and frequency of asthma exacerbations in children.Methods A cross-sectional study was carried out on asthmatic children aged 6 to 12 years in the Department of Child Health, Udayana University Medical School /Sanglah Hospital, Denpasar. Degree of sensitization was assessed by mean wheal diameter (positive defined as 3 mm greater than negative control) for seven common indoor allergens. Frequency of asthma exacerbation for three consecutive months prior to data collection was retrospectively reviewed.Results Positive skin test results for one or more allergens were found in 84 of 89 (94%) asthmatic children. Higher frequency of asthma exacerbations weakly correlated with the number of allergens with positive sensitization (r=0.284; P=0.007). Mean wheal diameter of each allergen did not correlate to the frequency of asthma exacerbations. In addition, the frequency of asthma exacerbations was independent for parental and sibling atopic history, preceding respiratory infections, use of asthma controllers and passive environmental tobacco smoke exposure.Conclusions Sensitization to common indoor allergens correlates weakly with frequency of asthma exacerbations.Â